The Effect of Performance Assessment and Incentives on Increasing Employee Achievement in PT. Indonesia Asahan Aluminium - Nadia Ika Purnama (Journal of International Conference Proceedings (JICP), 2021)
The importance of human resources for companies because it is the main factor where they have different emotions, feelings, desires and abilities, from which they have grown and developed so that a good level of work productivity can be achieved. Thus, it is necessary to integrate these aspects according to the needs of the organization. In this research will be discussed about performance appraisal and incentives as independent variables and work performance as the dependent variable with research at PT. Indonesia Asahan Aluminum. While the formulation of the research problem is: "How big is the influence of performance appraisal and incentives on improving employee performance at PT. Indonesia Asahan Aluminum ”. The purpose of this study was to describe the incentive program and work performance improvement implemented by PT. Indonesia Asahan Aluminum, to measure the level of work effectiveness of employees at PT. Indonesia Asahan Aluminum and to describe the significant level of influence of performance appraisals and incentives on improving employee performance at PT. Aluminum Asahan Indonesia. The results of this study indicate that the incentive program and work performance improvement implemented by PT. Indonesia Asahan Aluminum basically includes the provision of salaries and wages as well as overtime pay as well as the provision of social security for workers, in the form of old-age benefits, occupational health and safety benefits, bonuses and others. The level of work effectiveness of employees at PT. Indonesia Asahan Aluminum showed very significant results where from the results of the distribution of the questionnaire it was known that the answers given were quite valid and reliable. Meanwhile, from the test results, it is known that the calculated r value > from r table, namely rx 1 y = 0.772, rx 2 y = 0.631 and rx 1 x 2 = 0.548 > 0.423. So that the hypothesis is accepted, which means that there is an influence of the variable x 1 (performance appraisal) with x 2 (incentive) on the variable y (work performance) of employees at PT. Indonesia Asahan Aluminum . The significant level of influence of performance appraisal and incentives on improving employee performance at PT. Indonesia Asahan Aluminum is found in the coefficient interval 0.80 – 0.100, then the relationship between the variables x 1 (performance appraisal) and x 2 (incentives) and jointly correlated with the variable y (work performance) is included in the category of a very strong relationship with the value determination of 84.4%.